Global Geopolitical Dynamics: BRICS' Collective Strategy in Facing Western Domination and Its Implications for Indonesia - Valhan Hamdiana Rachman (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
This study aims to analyze the dynamics of global geopolitics through the collective strategy of the BRICS countries (Brazil, Russia, India, China, and South Africa) in facing Western domination, as well as to evaluate its implications for Indonesia from both political and economic perspectives. In the current multipolar era, BRICS seeks to strengthen its bargaining position through strategic cooperation in economics, finance, and global diplomacy. This study employs a qualitative approach using literature review methods, including the analysis of official documents, academic journals, and international news sources. The findings show that BRICS plays a strategic role in responding to Western dominance by enhancing multilateral cooperation, reforming global governance, and developing a more inclusive and alternative economic system. Initiatives such as the establishment of the New Development Bank (NDB), strengthening collective defense, and advancing renewable energy development reflect member states’ efforts to establish a more balanced world order. For Indonesia, BRICS presents significant opportunities in market access, infrastructure financing, and trade diversification. However, Indonesia must remain cautious of geopolitical challenges and the competition among emerging economies, and must formulate an adaptive foreign policy to fully capitalize on the benefits presented by these global shifts.